Sustainable Development, this Time Concept - Franciskovic Ingunza, Millitza (2015)
This article develops the way first studied from a scientific level, the problems that humanity begins to suffer more intensely on the planet in the fifties (population growth, industrialization, pollution).These studies are prepared by the international scientific community represented by an outstanding group of scientists from one of the world’s most prestigious academy, MIT (Massachusetts Institute of Technology). These scientists are those who are responsible for developing the first reports that contain numbers alarming of what was happening in the decade of the fifties, and what could happen to humanity in the very near future, with the aim of the rulers, responsible for leading their nations, take immediate action against the impending planetary catastrophe looks.